Physical disability in/and transcultural fandom: Conversations with my spouse. (1st March 2019) - Morimoto, Lori
This article, in contrast with more traditional forms of scholarly engagement, draws heavily on an interview I conducted with my spouse, who is a physically disabled fan of science fiction and fantasy, to help illuminate some of the complexities of my own area of research, transcultural fandoms. Often, when we write about disability and fandom (to the extent that we do at all), our emphasis is on issues of the accessibility of physical and virtual fan spaces. I take that up here as well, metaphorically sobbing over yet another mobility scooter damaged at the hands of possibly well-intentioned airline staff; but the article quickly comes to focus more on the multiple subjectivities that inflect any experience of fandom, including that of disabled fans. Particularly insofar as my spouse is a disabled Asian-American (Japanese/Korean) man and experiences fandom through the sometimes-conflicting lenses of race and ethnicity, disability, gender and functional heteronormativity, the experiences and impressions he recounts here reflect my own work on the fundamentally transcultural nature of fandoms and fans, in which 'culture' denotes not only nation-centred practices, but also those of the many subjectivities that comprise our identities.